2005
DOI: 10.1016/j.ejcts.2005.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous aortic valve replacement: resection before implantation☆

Abstract: Percutaneous resection of heart valves is emerging as a promising auxiliary method for the resection of calcified aortic heart valves because they can be cut endoscopically. Nonetheless, before this resection tool can be clinically applied by surgeons to perform a true percutaneous valve replacement, an additional aortic valve resection chamber (already at the prototype stage) designed for capturing all debris, has to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…The model developed in this study can easily be modified in order to generate a bicuspid valve, by a fusion of two leaflets for example, or can be combined to an experimental model of coronary flow to evaluate the impact of TAV on coronary circulation. Also, a device aiming at percutaneous aortic valve resection prior to TAVI can be tested on the model developed in this work [17]. Furthermore, the model can be useful for training, in vitro, surgeons on good positioning of TAV during implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The model developed in this study can easily be modified in order to generate a bicuspid valve, by a fusion of two leaflets for example, or can be combined to an experimental model of coronary flow to evaluate the impact of TAV on coronary circulation. Also, a device aiming at percutaneous aortic valve resection prior to TAVI can be tested on the model developed in this work [17]. Furthermore, the model can be useful for training, in vitro, surgeons on good positioning of TAV during implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our concept, Quaden et al reported on valve resection times of 2.3 AE 0.3 min up to 12.2 AE 0.8 min (per leaflet) with the use of a high-pressure water stream scalpel [15]. Recently, resection times of 6.0 AE 3.5 min per leaflet using a YAG laser device were reported [16].…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, transcatheter valve implantation has become a more widely available and accepted therapeutic procedure [17]. However, the idea to resect the diseased native aortic valve prior to the percutaneous aortic valve implantation procedure has been suggested by Quaden et al [15] in 2005, and to our knowledge, is so far the only study group working on this issue. Due to the fact that in transcatheter techniques, the pathology of the severely calcified aortic valve remains in situ and the aortic bioprosthesis has to be implanted in a severely calcified and rather asymmetric annulus, paravalvular leakages can be observed more frequently [18,19].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This strategy would be close to the 'gold standard' represented by the conventional prosthetic valve replacement that has been performed routinely for the past four decades. Strategies for the transapical resection of native aortic valve tissue have been examined and reported [58][59][60][61]. For example, a sophisticated method of in-situ transluminal resection of aortic valve leaflets using a YAG laser within an aortic valve isolation chamber has been developed.…”
Section: Experimental Transapical Implantation Of the Perceval S Valvementioning
confidence: 99%